Chemical Composition, Biological Activity, and Health-Promoting Effects of Withania somnifera for Pharma-Food Industry Applications - Javad Sharifi-Rad; Cristina Quispe; Seyed Abdulmajid Ayatollahi; Farzad Kobarfard; Mariola Staniak; Anna Stępień; Katarzyna Czopek; Surjit Sen; Krishnendu Acharya; Karl R. Matthews; Bilge Sener; Hari Prasad Devkota; et al. (Journal of Food Quality)
The Withania genus comes from the Solanaceae family and includes around 23 species, spread over some areas of the Mediterranean, Asia, and East Africa. Widely used in traditional medicine for thousands of years, these plants are rich in secondary metabolites, with special emphasis on steroidal lactones, named withanolides which are used as ingredients in numerous formulations for a plethora of diseases, such as asthma, diabetes, arthritis, impotence, amnesia, hypertension, anxiety, stress, cancer, neurodegenerative, and cardiovascular diseases, and many others. Among them, Withania somnifera (L.) Dunal is the most widely addressed species from a pharmacological and agroindustrial point of view. In this sense, this review provides an overview of the folk uses, phytochemical composition, and biological activity, such as antioxidant, antimicrobial, anti-inflammatory, and cytotoxic activity of W. somnifera, although more recently other species have also been increasingly investigated. In addition, their health-promoting effects, i.e., antistress, anxiolytic, adaptogenic, antirheumatoid arthritis, chemoprotective, and cardiorespiratory-enhancing abilities, along with safety and adverse effects are also discussed.